How long should Atrovent be given in acute asthma?. Issue 5 (1st May 1998) - Brophy, C; Ahmed, B; Bayston, S; Arnold, A; McGivern, D; Greenstone, M
Abstract : BACKGROUND: In acute asthma the optimal duration of treatment with combination β agonist and anticholinergic nebuliser solutions is unknown; most studies have investigated single doses or treatment for up to 12 hours. To determine whether longer treatment with ipratropium bromide might aid recovery a study was undertaken in 106 patients with acute asthma. METHODS: A double blind, randomised, placebo controlled, three group study was performed with all patients receiving ipratropium for 12 hours and salbutamol for 60 hours after admission (both nebulised four hourly), systemic steroids and, if necessary, theophylline. At 12 hours ipratropium was stopped in group I (n = 35) but was continued in the other two groups, and at 36 hours ipratropium was also stopped in group II (n = 35) while patients in group III (n = 36) continued with ipratropium for 60 hours. Spirometric tests were performed before and after salbutamol, and again 30 and 60 minutes after ipratropium or placebo at 12, 36 and 60 hours. Peak flow rates (PEFR) were measured before and after each nebulisation. RESULTS: There were no differences between the groups in PEFR on admission (group I: 214 l/min, group II: 198 l/min, group III: 221 l/min), or mean forced expiratory volume in one second (FEV1 ) at 12 hours (group I: 1.8 l, group II: 2.0 l, group III: 2.2 l), 36 hours (group I: 2.1 l, group II: 2.3 l, group III: 2.4 l), or at 60 hours (group I: 2.2 l, group II: 2.3 l, group III 2.5 l). Despite this, median time to discharge was significantly higher for patients in group I (5.4 days) than for those in groups II (4.1 days) and III (4.0 days). CONCLUSIONS: Combination nebulised therapy can be continued beyond 12 hours and up to 36 hours after admission with improved recovery time. Lung function testing may not reflect the full benefit of treatment.